Simple medium formulation for manganese remediation by green Microalga pediastrum duplex AARLG060 - Jakkapong Thongpitak (2018)
© 2018, Chiang Mai University. All rights reserved. Manganese is a heavy metal of significant interest to humans as it can have a potentially negative impact on the environment. Conventional methods for manganese removal such as chemical oxidation or ion exchange resin remain costly. Microalgae have been found to be a promising organism for manganese remediation by biosorption and bio-oxidation. This study is aimed at formulating an uncomplicated and economical medium for Pediastrum duplex cultivation. This medium has been found to enhance microalgal growth as well as to support the process of remediating soluble manganese in synthetic wastewater. It was found that the simple medium is comprised of four major nutrients: NaNO3, KH2PO4, NaHCO3and MnSO4. This medium has been found to be able to support microalgal growth similarly to the standard medium. Cultivation of microalgae in this medium resulted in removal of up to 93-95% manganese over 6 days. The results of this report will be used as the preliminary data for scaled studies on the remediation of manganese contaminated water using algal technology.